Non‐sebaceous lymphadenoma of the salivary gland with serous acinic cell differentiation, a first case report in the literature. (28th May 2013) - Ishii, Aya; Kawano, Hiroo; Tanaka, Shinsuke; Yamamoto, Yohei; Nakamoto, Tetsuya; Hirose, Yoshinobu; Yamashita, Hiroshi; Morinaga, Shojiroh; Ikeda, Eiji
Abstract : We report an atypical case of non‐sebaceous lymphadenoma (NSL) of the parotid gland showing serous acinic cell differentiation. NSL is a rare benign salivary gland tumor with intermingled lymphoid and epithelial tissues without sebaceous differentiation. Since the first description of a case designated by Auclair et al . as 'non‐sebaceous lymphadenoma' in 1991, to our best knowledge, only 37 cases have been reported, and no differentiation of tumor cells into serous acinic cell lineage has been described so far. In this paper, we present a case of NSL with serous acinic cell differentiation. The patient was a 78‐year‐old female with the complaint of a painless mass in the left parotid gland. The surgically resected tumor was encapsulated and measured 13 × 9 × 9 mm. Histologically, the tumor had the features of NSL, and an unusual finding of this case was the presence of epithelial cells with serous acinic cell differentiation. Dense cytoplasm packed with basophilic granules in those cells was positive in periodic acid Schiff reaction after diastase digestion (D‐PAS), which was compatible with the feature of serous acinic cell differentiation. Possible differentiation of the epithelial component into serous acinic cell in this rare entity is warranted to avoid confusion in the diagnosis.